'They have to abide by our laws … and stuff': ethnonationalism masquerading as civic nationalism. Issue 3 (July 2015) - Fozdar, Farida; Low, Mitchell
Abstract The long established distinction between civic nationalism and ethnonationalism is useful heuristically to understand different dimensions of nationalism and perhaps track a movement from ethnic forms to civic allegiances, though some have challenged its empirical veracity and others question the normative implications of such a distinction. This paper demonstrates the ways in which the two are elided in everyday discourses about migrants in Australia. We argue suspicion of cultural difference, identified more than three decades ago as the new racism, has given way to talk of the need for migrants to 'follow the law'. This serves rhetorically to reinforce the notion that migrants, often implied to overlap with the category 'Muslims', are insisting on breaking the law and/or changing it and are therefore culturally incompatible with a modern liberal democracy. We argue that since ethnic nationalism, like racism, is out of favour normatively, ethnic nationalist arguments are now superficially concealed beneath the acceptable language of civic nationalism. The manner in which this occurs is mapped discursively using data from a corpus of twenty seven focus groups conducted around Australia.